2012
DOI: 10.1167/iovs.11-9309
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clinically Invisible, but Optical Coherence Tomography Detected, Optic Disc Margin Anatomy on Neuroretinal Rim Evaluation

Abstract: BMO-MRW quantifies the neuroretinal rim from a true anatomical outer border and accounts for its variable trajectory at the point of measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
194
1
19

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(221 citation statements)
references
References 32 publications
7
194
1
19
Order By: Relevance
“…Although the accuracy of the measurement methods was validated by calculating the inter-visit and inter-observer reproducibilities, the disc-foveal angle from the disc photographs may have been slightly biased, given the fact that eyes have regionally variable extensions of Bruch's membrane inside the clinically identified disc margin that are photographically invisible (Chauhan et al 2012). However, the determination of the optic disc centre seems to be less affected by the inconsistency between disc margin and Bruch's membrane than the assessment of the neuroretinal rim (Reis et al 2012). Secondly, the overall posterior pole profiles of the PFS and PNS groups shown in this study might have been influenced by the proportion of superior and inferior involvement in each group, because PFS and PNS were also characterized according to superior and inferior VF defect in subgroup analysis.…”
Section: Commentsmentioning
confidence: 69%
“…Although the accuracy of the measurement methods was validated by calculating the inter-visit and inter-observer reproducibilities, the disc-foveal angle from the disc photographs may have been slightly biased, given the fact that eyes have regionally variable extensions of Bruch's membrane inside the clinically identified disc margin that are photographically invisible (Chauhan et al 2012). However, the determination of the optic disc centre seems to be less affected by the inconsistency between disc margin and Bruch's membrane than the assessment of the neuroretinal rim (Reis et al 2012). Secondly, the overall posterior pole profiles of the PFS and PNS groups shown in this study might have been influenced by the proportion of superior and inferior involvement in each group, because PFS and PNS were also characterized according to superior and inferior VF defect in subgroup analysis.…”
Section: Commentsmentioning
confidence: 69%
“…2,3 As further work is done comparing new imaging instruments, and attempts are made to standardize the measurements, other differences in methods will be relevant, such as differences in nature of the signal, image processing, segmentation of layers, reference planes, and the geometric strategy for rim width measurement. In this regard, several groups (most recently Reiss et al 3 ) proposed that rim width might be calculated advantageously in a ''minimum'' fashion (perpendicular to the trajectory of the axons) from the end of Bruch's membrane to the cup surface obliquely, instead of measured ''horizontally'' within different measurement planes that often are related to the termination of Bruch's membrane for OCT, but variably located for HRT. Making comparison more difficult is that any component of the rim measurement that occurs in the horizontal direction is influenced by the transverse magnification mentioned previously, but thickness measurements in the axial direction are not.…”
mentioning
confidence: 99%
“…[23][24][25] The disc margin is anatomically complex and studies have shown that the clinically identified disc margin is often based on more than one tissue structure. [26][27][28] It has been demonstrated that this variability can lead to a clinical disc margin assessment that may over-and/or underestimate the amount of remaining rim in any given optic disc region. 27,29 SDOCT technology allows crosssectional visualization of the neural canal opening, which provides a distinct advantage in identifying disc margins compared to traditional stereoscopic examination.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] It has been demonstrated that this variability can lead to a clinical disc margin assessment that may over-and/or underestimate the amount of remaining rim in any given optic disc region. 27,29 SDOCT technology allows crosssectional visualization of the neural canal opening, which provides a distinct advantage in identifying disc margins compared to traditional stereoscopic examination. This advantage is especially apparent in cases of optic nerve hypoplasia, where clinical identification of the disc margin can be very difficult.…”
Section: Discussionmentioning
confidence: 99%